Efforts To Build Moral Resilience By Reactualizing Pancasila Education In Generation Z In The Age Of The 4.0 Industrial Revolution - Rini Aristin; Hasbullah Hasbullah; Ria Kasanova (Journal on Education, 2023)
advancements. If this technology is not endowed with strong mental and spiritual abilities, this generation Z (students) will not be able to counteract its negative effects. In the worst case scenario, this effect will cause students to develop into a generation that forgets their identity, resulting in behavior that is inconsistent with Pancasila values. Based on this, the researcher conducted a study titled Efforts to Develop Moral Resilience through the Re-actualization of Pancasila Ethics in Generation Z in the Era of the Fourth Industrial Revolution. The research strategy is qualitative and descriptive, employing both purposive and accidental sampling. The data collection methods employed are interviews and observations. The results of the study indicate that Generation Z (students) already comprehend good ethics, specifically those that are in accordance with Pancasila, but the implementation is still hampered by the difficulties of the current era. There are two things that must be instilled in generation Z (students) in order to strengthen their moral resilience: 1) Building mental resilience; this can be accomplished by always comprehending, living, and demonstrating Pancasila values. 2) Strengthen spiritually; this can be accomplished by embracing and exercising religious principles.